Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Materi Himpunan untuk Kelas VII SMP Negeri I Loura (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the level of student errors in working on problems related to this material. The method used in this research is descriptive qualitative method, with the help of research instruments in the form of test question sheets, interview guidelines, scoring guidelines and documentation. Data collection was carried out by conducting tests and interviews with research subjects who were representatives of 16 students in total. The results of student work were then analyzed based on Newman Indicators, using analytical techniques which include data reduction, data analysis, data presentation and conclusion drawing stages. The results showed that the level of student errors in working on problems on set material was still categorized as high, characterized by students with high errors being more dominant than students in the low error category. Based on the results of research and discussion, it can be concluded that the work of seventh grade students of SMP Negeri 1 Loura in solving math problems on set material is still categorized as low.